Activated alpha 9 integrin expression enables sensory pathway reconstruction after spinal cord injury - Katerina Stepankova; Barbora Smejkalova; Lucia Machova Urdzikova; Katerina Haveliková; Fred de Winter; Stepanka Suchankova; Joost Verhaagen; Vit Herynek; Rostislav Turecek; Jessica Kwok; James Fawcett; Pavla Jendelova (Acta Neuropathologica Communications)
Abstract Full recovery from spinal cord injury requires axon regeneration to re-establish motor and sensory pathways. In mammals, the failure of sensory and motor axon regeneration has many causes intrinsic and extrinsic to neurons, amongst which is the lack of adhesion molecules needed to interact with the damaged spinal cord. This study addressed this limitation by expressing the integrin adhesion molecule α9, along with its activator kindlin-1, in sensory neurons via adeno-associated viral (AAV) vectors. This enabled sensory axons to regenerate through spinal cord injuries and extend to the brainstem, restoring sensory pathways, touch sensation and sensory behaviours. One of the integrin ligands in the injured spinal cord is tenascin-C, which serves as a substrate for α9β1 integrin, a key receptor in developmental axon guidance. However, the adult PNS and CNS neurons lack this receptor. Sensory neurons were transduced with α9 integrin (which pairs with endogenous β1 to form a α9β1 tenascin receptor) together with the integrin activator kindlin-1. Regeneration from sensory neurons transduced with α9integrin and kindlin-1 was examined after C4 and after T10 dorsal column lesions with C6,7 and L4,5 sensory ganglia injected with AAV1 vectors. In animals treated with α9 integrin and kindlin-1, sensory axons regenerated through tenascin-C-expressing connective tissue strands and bridges across the lesions and then re-entered the CNS tissue. Many axons regenerated rostrally to the level of the medulla. Axons grew through the dorsal grey matter rather than their normal pathway the dorsal columns. Growth was slow, axons taking 12 weeks to grow from T10 to the medulla, a distance of 4–5 cm. Functional recovery was confirmed through cFos activation in neurons rostral to the injury after nerve stimulation and VGLUT1/2 staining indicating new synapse formation above the lesion. Behavioural recovery was seen in both heat and mechanical sensation, as well as tape removal tests. This approach demonstrates the potential of integrin-based therapies for long distance sensory axon regeneration and functional recovery following thoracic and partial recovery after cervical spinal cord injury.